PERKAWINAN WNI DALAM MASA IDDAH DI LUAR NEGERI KETIKA KEMBALI KE INDONESIA DALAM BINGKAI HUKUM PERDATA INTERNASIONAL - Romli, Muhammad; Siti Khadijah, Yayu (Sekolah Tinggi Ilmu Fikih Syeikh Nawawi Tanara Serang, 2024)
Marriages conducted abroad must be based on the laws of the country where the marriage takes place, which have regulations in foreign countries. This is used as a loophole for Indonesian citizens who want to get married without having to wait for the Iddah period or waiting period. This research is a qualitative method with a statutory approach and data through library research. Data analysis uses content analysis and draws a conclusion. Based on research and discussion, the implementation of Indonesian citizens' marriages during the iddah period abroad, based on Article 56 and the principles of Indonesian International Civil Law, adheres to the principle of Lex Loci Celebrationis, where the marriage is conducted according to the law of the place where the marriage takes place. This formally indicates that the marriage is declared valid. However, as long as the cumulative requirements for international marriage as regulated in Article 56 have not been fulfilled, the marriage can still be considered invalid, and the legal status of Indonesian citizens' marriages during the iddah period abroad when returning to Indonesia does not yet have clear legal certainty from the applicable regulations.